2021
DOI: 10.1093/eurheartj/ehab724.0197
|View full text |Cite
|
Sign up to set email alerts
|

Pericoronary adipose tissue attenuation index (FAI) – a new imaging biomarker and its diagnostic and prognostic utility: a systematic review and meta-analysis

Abstract: Background Pericoronary fat attenuation index (FAI) on coronary computed tomography angiography (CCTA) imaging has been proposed as a sensitive marker of coronary vascular inflammation with prognostic value for major cardiovascular events. To date though there is no systematic review of the published literature and no meta-analyzed data of previously published results. Methods We performed a systematic review and meta-analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…PCAT is a fat deposit surrounding the coronary arteries. Inflammation of PCAT is associated with elevated HU intensity 1 , and various studies have shown that elevating HU of the PCAT region may be related to acute coronary syndrome or coronary artery disease 2,3 . Left ventricular function and volume measurement can augment cardiovascular risk prediction and discrimination for future mortality 4 .…”
Section: Introductionmentioning
confidence: 99%
“…PCAT is a fat deposit surrounding the coronary arteries. Inflammation of PCAT is associated with elevated HU intensity 1 , and various studies have shown that elevating HU of the PCAT region may be related to acute coronary syndrome or coronary artery disease 2,3 . Left ventricular function and volume measurement can augment cardiovascular risk prediction and discrimination for future mortality 4 .…”
Section: Introductionmentioning
confidence: 99%